Lateral skull base surgery the House Clinic atlas - Friedman, Rick A.; House Clinic (Thieme, 2012)
It is an insightfully organized text of advanced surgical techniques that will assist any training or practicing surgeon caring for those with acoustic schwannomas and other skull base pathology.